Odontoid incidence: a constant cervical anatomical feature evident in standing plain radiographs and supine magnetic resonance images - Huang, Longao; Chen, Weiyou; Xu, Hongyuan; Qin, Hongyu; Jiang, Hua (Journal of orthopaedic surgery and research, 2024)
To assess whether there is a difference between measurements of odontoid incidence (OI) and other cervical sagittal parameters by X-ray radiography and those by supine magnetic resonance imaging (MRI). Standing X-ray and supine MRI images of 42 healthy subjects were retrospectively analyzed. Surgimap software was employed to measure cervical sagittal parameters including OI, odontoid tilt (OT), C2 slope (C2S), C0-2 angle, C2-7 angle, T1 slope (T1S) and T1S-cervical lordosis (CL). Paired samples t-test was applied to determine the difference between parameters measured by standing X-ray and those by supine MRI. In addition, the statistical correlation between the parameters were compared. The prediction of CL was performed and validated using the formula CL = 0.36 × OI - 0.67 × OT - 0.69 × T1S. Significant correlations and differences were found between cervical sagittal parameters determined by X-ray and those by MRI. OI was verified to be a constant anatomic parameter and the formula CL = 0.36 × OI - 0.67 × OT - 0.69 × T1S can be used to predict CL in cervical sagittal parameters. OI is verified as a constant anatomic parameter, demonstrating the necessity of a combined assessment of cervical sagittal balance by using standing X-ray and supine MRI. The formula CL = 0.36 × OI - 0.67 × OT - 0.69 × T1S can be applied to predict CL in cervical sagittal parameters.